Agricultural Professionals’ Perceptions of COVID-19 and Occupational Health and Safety - Traci Irani; Beatrice Fenelon Pierre; Tyler S. Nesbit (Journal of International Agricultural and Extension Education, 2021)
The spread of the COVID-19 pandemic has brought tremendous challenges to citizens and industries worldwide. The present study contributed to efforts underway toward developing alternatives to combat COVID-19 in the agricultural industry, including the farm and forestry sectors. The study utilized qualitative interviews to assess the perceptions of agricultural stakeholders in the Southeastern United States on the impact of the pandemic to occupational health and safety and the likelihood of implementation of safety guidelines established by the Centers for Disease Control and Prevention (CDC). Eleven individuals, purposefully selected, were interviewed. The results suggested that despite its challenging aspects, the pandemic offers an array of opportunities to the industry to revamp operations and adjust approaches. The challenges related more to the uncertainties due to the unfolding elements of the pandemic. Transportation, housing, and culture were the top three barriers identified to implementing CDC guidelines. These barriers depend on the size of the companies, the types of operations, and the amount of required labor. Agricultural stakeholders' positive behavior, the availability of incentives, and the use of innovation, including technology, were revealed to be the three main supportive factors relating to the execution of the CDC guidelines. These results could evolve as the pandemic continues to unfold. Therefore, we suggest that continuing assessments be conducted to capture shifting perceptions and attitudes as they change to reflect updated information. Further investigations about the side effects of mask-wearing on heat-related illnesses were also advised to explore in terms of guidelines for agricultural workers
Keywords: COVID-19; agriculture; health; safety; guidelines